Implementasi Program Kartu Sehat Bekasi dalam Pemenuhan Hak Kesehatan Masyarakat - Rahman, Reyhatul Jannah Aprilia; Hendrijanto, Kris (University of Jember, 2021)
The Government of Bekasi City has designed a regional health insurance program to respond community complaints about the lack of equal distribution of health insurance provided by the central government. Therefore, the regional government has responsibility in fulfilling health insurance, especially regional health insurance. The government of Bekasi city strives for distributing regional health insurance through a program called Kartu Sehat Bekasi, so the community is able to be fulfilled their health insurance. This is an effort to respond to community problems and needs regarding the lack of equal distribution of Health Insurance provided by the Central Government. The equal distribution will be fulfilled by the Regional Government. The implementation process starts from preparation, implementation, and evaluation. The implementation of Kartu Sehat Bekasi is carried out by the Puskesmas in the Bekasi city as the first reference level; the Hospital in collaboration with the Bekasi City government as the level of advanced reference; and Bekasi City Health Office as the party that assists in implementing the program to issue administrative needs. This descriptive research employed qualitative approach. The informants were determined by using purposive technique. Research data were collected through observation, interviews, and documentation. Then, the data were analyzed by using data reduction, data presentation, and verification. To test data validity, researchers used source triangulation technique. The findings revealed that the fulfillment of the health rights in Bekasi city in implementing Kartu Sehat Bekasi program was in the form of the easy access to health services and quality of health services felt by the community. Moreover, the rights to health services were not only for themselves but also for family members. Furthermore, the number of patients each year increases, but the procedure application has not been maximized, and also people were still unwilling in administrative matter as the inhibiting factor. Hence, a community empowerment activity was needed in Kartu Sehat Bekasi program to create an independent community in terms of health, and it did not depend on health insurance provided by the government.